The effect of the SUMPING E-module as a labor companion on the duration of labor in independent midwife practice - Utami Dewi; Rahmadona Rahmadona; Nurniati Tianastia Rullyni; Rully Hevrialni (Healthcare in Low-resource Settings, 2024)
Reducing the incidence of childbirth complications requires family participation, especially from husbands, consistent with government policies and strategies aimed at reducing childbirth complications in Indonesia through the Making Pregnancy Safer (MPS) program. The approach to increasing husbands' involvement in reproductive health includes providing them with information and involving them in all efforts to improve reproductive health. One activity husbands can undertake to improve maternal and child health is accompanying their wives during labor and supporting referrals when necessary. The purpose of this study was to determine the effect of labor assistance using the SUMPING (Supporting Husband as a Companion) E-Module compared to labor assistance without using the SUMPING E-Module on the duration of labor. The research design was a quasi-experiment with a control group that only underwent the post-test. The instruments used included a checklist and a partograph sheet. Data collection occurred during the post-test. The study involved 120 respondents, all of whom were birth attendants (husbands) at PMB Tanjungpinang. Analysis was conducted using the Independent Samples t-test. Statistical tests using the independent samples t-test revealed a significant difference (p=0.000) in the length of labor between those with full and those with non-full assistance in the treatment group. In the control group, there was no significant difference (p=0.039) between husbands who provided full assistance and those who did not. Husband support can shorten the duration of labor. Husbands who had access to the SUMPING E-Module reported greater involvement in assistance during labor than those without the SUMPING E-Module.